Coke formation during rapid quenching of volatile vapors from fast pyrolysis of cellulose. (15th December 2021) - Li, Bin; Xie, Xing; Zhang, Lei; Lin, Dan; Wang, Shuaijun; Wang, Shuang; Xu, Huibin; Wang, Junfeng; Huang, Yong; Zhang, Shu; Liu, Dongjing
Graphical abstract: Highlights: Coke formation during rapid quenching of cellulose pyrolysis volatiles was studied. Yield and structure of coke were correlated to pyrolysis T and volatile composition. Less coke formed when quenching volatiles form lignin and xylan than from cellulose. Interactions between anhydrosugars and aldehydes/ketones are likely coking pathways. Coke with O of ~41–46% was thermally unstable and more aliphatic than polyaromatic. Abstract: Coke formation during the rapid quenching of volatiles produced from fast pyrolysis of cellulose was investigated in a fixed-bed reactor. The coke sample was collected at the reactor outlet. The chemical structure of the coke was characterized with a Fourier Transform Infrared spectroscopy (FTIR) and a Raman spectroscopy. The thermal stability of the coke was determined with a thermogravimetric analyzer. The results showed that the coke yield decreased from 19.70 wt% to 14.10 wt% with the pyrolysis temperature increasing from 400 to 600 °C. A high oxygen content of 41.31–46.04 wt% was observed for the cokes which was quite similar as that of volatiles, illustrating the close relationship between volatile composition and coke formation. The FTIR results showed that the coke contained abundant oxygen-containing functional groups such as alcohol O–H, aldehydes/ketones CO and alcohol/ether C–O, and aliphatic C–H groups. With the combination of the Raman spectroscopy results, the coke structure appeared to be more aliphatic than polyaromatic. Changes in pyrolysis temperature would alter the coke properties by changing the volatile composition. The dominant coking reactions were finally inferred as the condensation/polymerization of anhydrosugars and aldehydes/ketones.